EVALUATION OF POSSIBILITIES TO IMPROVE RIGID BODIES - Nurullayev Н.М; Turgunboyev Д.А; Zholdassov Е.Н (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Manipulators are used for various purposes in order to simplify tasks or reduce the risk of tasks that are considered impossible, dangerous or difficult for humans. The robotic arm can be equipped with various types of end effectors to perform a variety of tasks. Grips are one of the most commonly used tools for manipulators. This article discusses the analysis of modeling new robotic gripping fingers, based on models of gripping gross rigid bodies of manipulators. A literature review was conducted in the relevant branches of scientific research. The ability to minimize dimensions and masses, as well as the final cost of the product, using available materials and electromechanical devices, various sensors, is evaluated. The external characteristics that make the previously developed analogues ineffective are analyzed. Modeling was released using the SolidWorks software package.